FACTORS AFFECTING EMPLOYEE PERFORMANCE IN BANK EMPLOYEES BATAM CITY - Razak, Indra Miftahul; Priscilla, Yuddy Giovanna (Institut Teknologi dan Bisnis Asia Malang, 2024)
The study examines the influence of Talent Management, knowledge management, career development, motivation, and competence on employee performance. The object of this research is an employee at a bank in Batam City. The data used was primary data and using Google Forms and collected as many as 233 respondents through the dissemination of questionnaires. The application of SPSS (Statistical Product and Service Solutions) is used as a test tool and the results of research show that talent management and knowledge management have significant and acceptable bets, while on motivation, career development, and competence have insignificant or unacceptable results after the test. This research recommends that this study be developed with the added variables and is expected to support the improvement of employee performance in order to create more potential human resources to create corporate competitiveness.